HYBRID FINANCING INSTRUMENTS IN THE EARLY STAGES OF STARTUPS IN SERBIA AND GERMANY - ADVANTAGES AND DISADVANTAGES - Zivkovski, Igor; Djurdjevic, Aleksandar (Glasnik Advokatske komore Vojvodine, 2020)
Development and growth of the startup industry worldwide has lead to the creation of various financing instruments. In addition to the traditional financing instruments – debt financing and equity financing, business practice has given rise to the cration of financing instruments that have the elements of both debt and equity. Those instruments are referred to as hybrid financing instruments, or, in other words, mezzanine capital instruments. The core advantage of these instruments is their flexibility in structuring of the financing rounds, as well as the fact that the investors, who have a strong bargaining position in early stage financing, can obtain higher levels of control of their investment, while not exposing themselves to the unnecessary risk. The authors of this article comparatively analyze hybrid financing instruments that are used in startup financing in Serbia and in Germany.
Keywords: startup; investment; , hybrid financing instruments; mezzanine capital; Serbia; Germany